Representational Mind A Study of Kant's Theory of Knowledge - Aquila, Richard E. (Indiana University Press, 1983)
While many works on Kant's theory of knowledge place primary emphasis on assessing the validity of Kant's arguments, Richard E. Aquila aims first at clarifying the meaning of basic claims and concepts as Kant himself understood them. Representational Mind offers an interpretation of some of the most fundamental epistemological distinctions that Kant drew: between matter and form, intuition and concept, and things in themselves and appearances. Aquila's analysis centers on a theory of consciousness as the conceptual determination of intentional objects, the structure of which is grounded in forms of intuition. This approach, which distinguishes between concepts as mere predicates of judgments and as representations that phenomenologically inform intuitions, leads to a fuller grasp of the role of conceptualization in thinking. Shedding new light on the meaning of Kant's Transcendental Aesthetic, Aquila also gives extended treatment to imag- ination and schematism. The concluding chapter is devoted to the problem of self- awareness and the flow of time . An important contribution to the dialogue between phenomenological and analytical perspectives, Representational Mind will be of interest to scholars and students concerned with the history of modern philosophy and with philosophical problems involving the nature of mind and the intentionality of consciousness.